2012
DOI: 10.4067/s0718-95162012005000030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil organic carbon and dissolved organic carbon in Robina pseudoacacia forests

Abstract: We investigated the variation patterns of organic carbon in soil and soil solution of four selected Robinia pseudoacacia forests aged 10a, 25a, 31a, and 35a, as well as a contrastive tillage site in a similar topography condition in Loess Plateau, China. The purpose was to explore the dynamics of soil organic carbon (SOC) and dissolved organic carbon (DOC) in R. pseudoacacia forests. On average depths of 20, 40, and 60 cm, SOC, active organic carbon (AOC), and DOC gradually increase with increased forest age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Litter decomposition influences soil biogeochemistry of plant stands and affects the formation of soil organic matter (SOM). Due to its decomposability litter affects organic carbon accumulation in the soil and, consequently, stabilization of SOM (Lv and Liang, 2012). Differences across ecosystems are the result of different climates, varying litter input into the soil (Aranda and Comino, 2014), and changing availability of litter carbon for decomposition and potential carbon stabilization in soil (Six et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Litter decomposition influences soil biogeochemistry of plant stands and affects the formation of soil organic matter (SOM). Due to its decomposability litter affects organic carbon accumulation in the soil and, consequently, stabilization of SOM (Lv and Liang, 2012). Differences across ecosystems are the result of different climates, varying litter input into the soil (Aranda and Comino, 2014), and changing availability of litter carbon for decomposition and potential carbon stabilization in soil (Six et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because plant roots made significant contributions to soil carbon under grassland (McNally et al, 2015). Lv and Liang (2012) also found that during forest restoration, SOC did not consistently increase linearly with restoration years.…”
Section: Discussionmentioning
confidence: 88%
“…Artificial grassland establishment also significantly improved SOC in the topsoil (Wu et al, 2010). So reclamation of drastically disturbed mine soil and subsequent planting trees or grass could rapidly build-up carbon in the soil (Nyamadzawo et al, 2008;Lv and Liang, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…However, land use change affects soil morphological, physical, chemical and biological properties, as it changes both the type of vegetation and the nature of the agrotechnical measures applied (Prokofeva, Poputnikov, 2010;Kalinina et al, 2013;Novikova, Konyushkova, 2013). Lv and Liang (2012) propose that by reducing the anthropogenic load and the intensity of the economic activity, due to agroecosystem self-regulation and prevailing zonal paedogenic processes, the soil partially regains its original condition, although it does not fully recover its natural properties. Signs of agrogenic activities in the soil profile can be recorded 100 years after the cessation of agrarian activities (Kalinina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%